2010
DOI: 10.1097/hjr.0b013e32833a1c95
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nonpharmacological secondary prevention of coronary heart disease

Abstract: Nonpharmacological secondary prevention is safe and effective, with exercise and multimodal interventions reducing mortality most substantially. There is a lack of studies concerning dietary and smoking cessation interventions. In addition, intervention effectiveness in patient subgroups and of intervention components could not be evaluated conclusively. Future research should investigate these issues in rigorous studies with appropriate follow-up duration to improve the current poor risk factor control of CHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 59 publications
(120 reference statements)
2
34
0
7
Order By: Relevance
“…Therefore, it is of crucial importance that new therapeutic strategies are not only aimed at improving the health status of cardiovascular patients but also at prevention of future cardiac events and hospitalisation. As such, exercise-based cardiac rehabilitation (ECR) after an acute coronary syndrome (ACS), coronary revascularisation and in patients with chronic heart failure (CHF) has been shown to be a highly effective treatment, improving exercise capacity and quality of life, while reducing the risk of recurrent cardiovascular events and mortality [3,4]. Therefore, exercise training in these patients is now recommended in both national and international guidelines [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of crucial importance that new therapeutic strategies are not only aimed at improving the health status of cardiovascular patients but also at prevention of future cardiac events and hospitalisation. As such, exercise-based cardiac rehabilitation (ECR) after an acute coronary syndrome (ACS), coronary revascularisation and in patients with chronic heart failure (CHF) has been shown to be a highly effective treatment, improving exercise capacity and quality of life, while reducing the risk of recurrent cardiovascular events and mortality [3,4]. Therefore, exercise training in these patients is now recommended in both national and international guidelines [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review reported a 27% (odds ratio [OR]: 0.73; 95% confidence interval [CI]: 0.54 to 0.98) reduction in total mortality and 19% reduction (OR: 0.81; 95% CI: 0.65 to 1.01) in total mortality and non-fatal cardiac events with exercise-only CR, with slightly lower but comparable effects of comprehensive CR [5]. More recent meta-analyses suggest even stronger effect, with halving of mortality for any type of CR [6]. CR programs compare favorably to effective pharmacological treatments for secondary prevention of CVD (e.g.…”
Section: Definition and Indications Of Cardiac Rehabilitationmentioning
confidence: 99%
“…statins and beta-blockers). Among its component interventions, evidence suggest that exercise may have a stronger effect on mortality, while psychological interventions act more on quality of life measures; evidence on the other component of CR or the nature of exercise that produce the most benefit is limited [6].…”
Section: Definition and Indications Of Cardiac Rehabilitationmentioning
confidence: 99%
“…40,41 In addition, psychological interventions do appear to be effective in reducing both depression and anxiety. Psychological interventions were also found to be most effective in reducing depression when they included an intent to treat type-A behaviors; however, interventions focusing on a) education about cardiac risk factors, b) emotional support through client discussion and c) included family members in the treatment process were significantly less effective in affecting depression.…”
Section: Psychosocial Interventionmentioning
confidence: 99%